Avaliação inicial de videiras sob enxertia de mesa - Dall'Oglio, Paulo Antonio (2015)
The bench grafting allowed anticipate the first vineyard harvest. The objective of this research was evaluated the development of American native grapes (Bordô, Isabel Precoce and Niagara Rosada) in rootstocks (IAC-766 Campinas and 420-A) under bench grafting in west of Paraná state. The experiments were conducted in private proprieties at Toledo (2010/ 2011) and Ouro Verde do Oeste-PR (2014/ 2015) and shared in two phases: In the first phase was evaluated the plant formation through union between graft and rootstock, percentage of rooting, average height of sprouting and survive after transplantation field. In second phase the parameters consisted of diameter of horizontal cordon, number of grow plants, number of gems and number of branches than reach the second and third line of the support system. At Toledo only the last parameter (number of branches that reached the second and third line of the support system) showed significant influence. The IAC-766 was more vigorous than 420-A. In the second experiment, the local factor doesn't show showed influence when the researches were analyzed together confirming the results the first research. Both rootstocks are able to cultivate in west of Paraná State, although IAC-766 was more vigorous than 420-A